การประเมินประสิทธิภาพของสูตรตำรับพืชสมุนไพรไทยในการต้านภาวะผมร่วง - พัชริดา เพ็ญภาคกุล (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2020)
The aims of this study are to evaluate the efficacy of Thai herbal extracts against hair loss and to develop herbal formulations for treating hair loss. Phytosterol extracts and flavonoid extracts from 6 medicinal plants including Nom-wau (Uvaria rufa Blume), Nom-maew (Anomianthus dulcis (Dunal) J. Sinclair), Nom-kwai (Artabotrys harmandii Finet & Gagnep.), Kled-pla-chon (Phyllodium pulchellum), Fang (Caesalpinia sappan L.) and Tum-leung (Coccinia grandis) were examined for their anti-hair loss effects by 3 in vitro analysis, the assessment of hair follicle elongation, 5α-reductase inhibitory activity and antioxidant activity. The most effective extracts in in vitro studies were flavonoid extracts from Nom-wau, Nom-maew, Fang and Kled-pla-chon as well as phytosterol extract from Nom-Kwai. Fifteen anti-hair loss formulas were prepared from those extracts and then tested for their activities in promoting hair follicle elongation and inhibiting 5α-reductase activity. The results showed that there were 2 potent formulas with anti-hair loss activity, formula 1 and formula 5. The formula 1 is composed of flavonoid extracts from Kled-pla-chon Fang and Nom-wau with a proportion of 1:3:1 and the formula 5 is composed flavonoid extracts from Kled-pla-chon Fang and Nom-wau with a proportion of 4:0.5:0.5. Theses 2 formulas were selected for in vivo evaluation of anti-hair loss activity. The obtained results were compared with those of synthetic drugs; finasteride and minoxidil. Our results demonstrated that mice treated with both formulas regrew their hair faster than control mice. Mice treated with formula 1 and formula 5 exhibited initial hair regrowth on day 14 and day 21 of the experiment, respectively. Also, the group treated with formula 5 showed the highest density of hair follicles as compared to other groups and their hair were all in anagen stage. Both formulas significantly increased antioxidant levels and significantly decreased lipid peroxidation in the skin tissues as compared to the negative control. In addition, both formulas effectively inhibited 5α-reductase activity since they significantly promoted skin tissue testosterone as the same level as finasteride. Thus, both formulas which consisted of flavonoid extracts from Kled-pla-chon, Fang and Nom-wau have potent anti-hair loss effects by inducing hair regrowth, inhibiting oxidative stress, and inhibiting 5α-reductase. Also, the formulas could be further developed into anti-hair loss products.